Mission Invisible A Novel About the Science of Light - Leonhardt, Ulf.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Invisibility has fascinated people since time immemorial, but only a decade ago did invisibility become a serious subject of scientific investigation. This lively novel, authored by an expert in the field, takes the reader on a journey to fascinating places and - en passant - on an intellectual adventure involving some of the most fascinating subjects of optics. While enjoying the fun and action of a travel story, the reader will gain an accurate notion of the real science of invisibility, of the light and shade of the business of science, as well as glimpses into different cultures. From the first page, you will gradually become immersed in a different world, the world of the science of light. The book includes an appendix providing interested readers with deeper insights into the fundamental physics of space-time, gravity and light.
Keywords: Physics; Optical materials; Electronic materials; Lasers; Photonics; Popular Science in Physics; Optical and Electronic Materials; Optics, Lasers, Photonics, Optical Devices